Investigation of Inactive-State κ Opioid Receptor Homodimerization via Single-Molecule Microscopy Using New Antagonistic Fluorescent Probes - Drakopoulos, Antonios; Koszegi, Zsombor; Lanoiselée, Yann; Hübner, Harald; Gmeiner, Peter; Calebiro, Davide; Decker, Michael (Journal of Medicinal Chemistry, 2020)
Opioid receptors (ORs) are among the best-studied G protein-coupled receptors due to their involvement in neurological disorders and important role in pain treatment. Contrary to the classical monomeric model, indirect evidence suggests that ORs might form dimers, which could be endowed with a distinct pharmacological profile, and, thus, be targeted to develop innovative pharmacological therapies. However, direct evidence for the spontaneous formation of OR dimers in living cells under physiological conditions is missing. Despite a growing interest in the κ opioid receptor (KOR), KOR-selective fluorescent probes are particularly scarce in the literature. Herein, we present the first set of fluorescent KOR-selective probes with antagonistic properties. Two of these were employed in single-molecule microscopy (SMM) experiments to investigate KOR homodimerization, localization, and trafficking. Our findings indicate that most KORs labeled with the new fluorescent probes are present as apparently freely diffusing monomers on the surface of a simple cell model.
CRIS-Team Scopus Importer:2020-04-21